Open Science-friendly national R&D knowledge and information infrastructure: A case study from Korea - Shmagun, Hanna; Shim, Jangsup; Oppenheim, Charles; Choi, Kwangnam; Chun, Kwangho; Kim, Jaesoo (Septentrio Conference Series, 2022)
This paper outlines the functionality of the South Korea’s National Science and Technology Information Service (NTIS), maintained by the Korea Institute of Science and Technology Information (KISTI). NTIS is a “one-stop shop” portal federating information on national R&D projects from multiple databases and metadata aggregators, including links to downloadable Open Access outputs and raw data. Among other functions, it provides a range of services based on R&D information analysis to facilitate open collaboration and knowledge co-development (e.g., providing network maps visualising collaboration among researchers and research institutes based on the field of research interest). In addition, some challenges associated with NTIS are outlined, including a lack of explicit Open Science mandates in national legislation and policies. We also suggest some opportunities for further development of the NTIS platform so that it can better support Open Science. These include, for example, alternative research impact metrics and a virtual laboratory service to be embedded into the NTIS functionality. Insights offered in this paper regarding the Korean experience of building an Open Science infrastructure could be useful to anyone planning to establish an R&D knowledge and information infrastructure, including various Open Science building blocks, in other contexts and countries.